Changes in efflux pump activity of Clostridium beijerinckii throughout ABE fermentation - Branska, Barbora; Vasylkivska, Maryna; Raschmanova, Hana; Jureckova, Katerina; Sedlar, Karel; Provaznik, Ivo; Patakova, Petra (Applied microbiology and biotechnology, 2021)
Pumping toxic substances through a cytoplasmic membrane by protein transporters known as efflux pumps represents one bacterial mechanism involved in the stress response to the presence of toxic compounds. The active efflux might also take part in exporting low-molecular-weight alcohols produced by intrinsic cell metabolism; in the case of solventogenic clostridia, predominantly acetone, butanol and ethanol (ABE). However, little is known about this active efflux, even though some evidence exists that membrane pumps might be involved in solvent tolerance. In this study, we investigated changes in overall active efflux during ABE fermentation, employing a flow cytometric protocol adjusted for Clostridia and using ethidium bromide (EB) as a fluorescence marker for quantification of direct efflux. A fluctuation in efflux during the course of standard ABE fermentation was observed, with a maximum reached during late acidogenesis, a high efflux rate during early and mid-solventogenesis and an apparent decrease in EB efflux rate in late solventogenesis. The fluctuation in efflux activity was in accordance with transcriptomic data obtained for various membrane exporters in a former study. Surprisingly, under altered cultivation conditions, when solvent production was attenuated, and extended acidogenesis was promoted, stable low efflux activity was reached after an initial peak that appeared in the stage comparable to standard ABE fermentation. This study confirmed that efflux pump activity is not constant during ABE fermentation and suggests that undisturbed solvent production might be a trigger for activation of pumps involved in solvent efflux. KEY POINTS: • Flow cytometric assay for efflux quantification in Clostridia was established. • Efflux rate peaked in late acidogenesis and in early solventogenesis. • Impaired solventogenesis led to an overall decrease in efflux.
Keywords: Ethanol; Acetone; Flow cytometry; aceton; Clostridium beijerinckii; ethanol; Fermentation; butanoly; Clostridium; ABE fermentation; Ethidium bromide; fermentace; Efflux pump; Butanols